Ferro- and ferrielectricity and negative piezoelectricity in thioamide-based supramolecular organic discotics - Urbanavičiūtė, Indrė; Garcia-Iglesias, Miguel; Gorbunov, Andrey; Meijer, E. W.; Kemerink, Martijn (Physical chemistry, chemical physics, 2023)
Amide-based discotic supramolecular organic materials are of interest for fundamental understanding of cooperative self-assembly and collective dipole switching mechanisms as well as for practically relevant ferroelectric and piezoelectric properties. Here, we show how replacing amides (dipole moment of ∼3.5 D) with thioamides (∼5.1 D) as dipolar moieties in the archetypal C3-symmetric discotic molecule BTA leads to ferroelectric materials with a higher remnant polarization and lower coercive field. The thioamide-based materials also demonstrate a rare negative piezoelectricity and a previously predicted, yet never experimentally observed, polarization reversal via asymmetric intermediate states, that is, ferrielectric switching.